Anthrax: Deadly Bioterrorism Threat and Prevention Challenges in Indonesia - Vicennia Serly; Yessy Susanty Sabri (Green Publisher Indonesia, 2025)
Anthrax is a disease caused by the bacterium Bacillus anthracis. The disease can be a threat to bioterrorism because it causes a high mortality rate and is easy to spread. The characteristics of sport anthrax are resistance to extreme environmental conditions. Furthermore, the Vegetative form of anthrax bacteria can form biofilms. This characteristic causes the bacteria to become a potential biological weapon agent because it is persistent and resistant to some antimicrobial agents. Antibiotic therapy is still considered the main treatment choice for anthrax disease. Antibiotic recommendations vary depending on the location, severity of the disease, and level of antimicrobial sensitivity that should be tested through bacterial culture. Anthrax prevention and control procedures in Indonesia are still limited in monitoring the entry of animals from anthrax-free areas and administering vaccines to animals in endemic or enzootic areas. The high rate of death, illness, and economic burden due to anthrax outbreaks requires health workers to increase medical vigilance against clinical anthrax. Early detection efforts and policy-making to prevent the spread of anthrax, especially against the possibility of its use as bioterrorism, should be a concern